Pengembangan Sistem Informasi Keuangan Pegawai Biro Organisasi Sekretariat Daerah Provinsi Jawa Timur - Luluk Mukarromah; Fajar Pradana; Mochamad Chandra Saputra (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
The financial management of employees at Biro Organisasi of East Java Provincial Government is still less efficient. Efficiency improvement of employee financial management can be achieved with the support of information system. Research on the development of employee financial information systems is to produce an information system that can improve the efficiency of employee financial management. The development method that used in developing this information sistem is Rational Unified Process (RUP). Business process as-is, business process to-be, fitur, functional and nonfunctional requirement will be modeled in inception phase. The elaboration phase produces a use case according to the features that have been identified and will be used for modeling design diagrams such as activity diagrams, sequence diagrams, and algorithmic design. While the results of the analysis class diagram modeling will be used as the basis for making the design and physical data model class. After implementing system according to design, testing of the employee's financial information system will be carried out. The test results reveal that the information system runs according to requirements and can be easily used by users.